From Post-Colonialism to Transnationalism: the Challenges for Post-Socialist Feminist Theory - Jambrešić Kirin, Renata (Poznańskie Studia Slawistyczne, 2016)
The article offers a reflection on the utility of postcolonial studies and transnational feminism for the analysis of women’s post-socialist experiences, with a special emphasis on Croatian academic and social space. After general considerations about the epistemological profile and etico-political agenda of transnational feminism – as illustrated by the results of the feminist seminar in Dubrovnik (2007–2015) – the author presents three theoretically most challenging feminist authors: Madina Tlostanova, Biljana Kašić and Marina Gržinić. Each of them in its own way demonstrates that theoretical voices from the “global South” are the most productive tool to oppose academic “global feminism” and to inspire “women’s struggles for sociopolitical justice, especially in colonial and neocolonial contexts” (Swarr, Nagar 2010: 4). The radical call for the decolonization of gender, human being and knowledge (Tlostanova 2013), the appreciation of woman’s public voices and counter-discourses (Kašić), and the critique of racialization in the production of knowledge (Gržinić 2015) are intertwined and linked to the final thesis about the importance of distinguishing the biopolitical form of women’s memory vs. the necropolitical formation of institutionalized history in post-socialist context.